The effect of sleep quality due to stress on medical students' academic achievement: A cross-sectional study - Arini Dyah Saputri; Imelda Ritunga (Health for All Nations, 2023)
Stress on students can cause a decrease in sleep quality and potentially reduce academic achievement. Understanding the effect of stress-induced sleep quality on academic achievement allows for selecting the most appropriate intervention. This study aimed to determine the impact of sleep quality due to stress on the academic achievement of medical students at Universitas Ciputra Surabaya. The method used in this study is quantitative research in the form of analytic observational with a cross-sectional approach. Sampling was done by using a random sampling technique. The population is 80 students from the Faculty of Medicine at the Universitas Ciputra Surabaya, third year and fourth year medical students. The sample size in this study was 63 students. Data was collected using the Depression Anxiety Stress Scale-21 (DASS-21) questionnaire to measure stress levels and the Pittsburgh Sleep Quality Index (PSQI) questionnaire to measure sleep quality. Sampling was only done with the consent of the respondent. The data analysis used was the correlation test which was carried out to determine the relationship between sleep quality and stress levels; the linear regression test was carried out to assess the effect of sleep quality due to stress on academic achievement. All respondents experienced stress and sleep disturbance to various degrees. The highest proportion was mild stress and moderate sleep disturbance, respectively, 50.8% and 73%. Correlation test results showed a significant relationship between sleep disturbances and stress levels (r= 0.29; p= 0.021), and the linear regression test results showed no effect of sleep quality due to stress on academic achievement (p= 0.241). Based on the data analysis, it can be concluded that the decrease in sleep quality due to stress does not affect academic achievement in medical students.